Pengaruh E-Marketing dan E-Crm Terhadap E-Loyalty Website Usaha Komunikasi Pemasaran - Filo Novandi Prasetya; Idris Gautama So (Binus Business Review, 2014)
Website traffic levels become an important thing for Marketing Communication firm in order to obtain and retain its customer. E-loyalty is necessary, in this case, to increase the website traffic level. This study was conducted to examine the influence of e-marketing and e-CRM towards e-loyalty in the non e-commerce website owned by Marketing Communication firm either individually or simultaneously based on relationship existence between each variable that would be proven its influence. The method used in this study is multiple linear regression for hypothesis testing and correlation test and descriptive statistic analysis. The results show that emarketing and e-CRM related and provided an influence towards e-loyalty individually or simultaneously.